2020
DOI: 10.1093/mnras/staa577
|View full text |Cite
|
Sign up to set email alerts
|

A possible distance bias for type Ia supernovae with different ejecta velocities

Abstract: After correcting for their light-curve shape and color, Type Ia supernovae (SNe Ia) are precise cosmological distance indicators. However, there remains a non-zero intrinsic scatter in the differences between measured distance and that inferred from a cosmological model (i.e., Hubble residuals or HRs), indicating that SN Ia distances can potentially be further improved. We use the open-source relational database kaepora to generate composite spectra with desired average properties of phase, light-curve shape, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 84 publications
6
15
0
Order By: Relevance
“…In fact, there are indications that there are two SN populations, having different SN ejecta velocities and different intrinsic colors, which also trace the host galaxy stellar mass (see e.g. Polin et al 2019;Siebert et al 2020;Pan 2020). Childress et al (2013) and Gonzalez-Gaitan et al ( 2020) simulate the effect of having separate colorluminosity corrections for low-and high-mass galaxies.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are indications that there are two SN populations, having different SN ejecta velocities and different intrinsic colors, which also trace the host galaxy stellar mass (see e.g. Polin et al 2019;Siebert et al 2020;Pan 2020). Childress et al (2013) and Gonzalez-Gaitan et al ( 2020) simulate the effect of having separate colorluminosity corrections for low-and high-mass galaxies.…”
Section: Discussionmentioning
confidence: 99%
“…This is critical to remo v e contamination from core-collapse SNe and other non-SN Ia transients. Several studies in the literature have demonstrated that SNe Ia can be divided into subclasses based on spectral line velocities near maximum light, with potential implications for distance measurements (Wang et al 2009 ;F ole y & Kasen 2011 ;F olatelli et al 2013 ;Siebert et al 2020 ;Dettman et al 2021 ). Therefore, having spectra is important for improving cosmological inference with SNe Ia.…”
Section: Spectr Oscopic Pr Opertiesmentioning
confidence: 99%
“…SN velocity is an active topic of investigation in the SN Ia community, with hints that high and low-velocity SN Ia vary in their intrinsic colors and intrinsic color scatter (e.g., Foley et al 2011;Foley 2012;Mandel et al 2014;Pan et al 2015;Siebert et al 2020). This correlation motivated the inclusion of a velocity perturber in our simulations.…”
Section: Ejecta Velocity Perturbermentioning
confidence: 96%
“…Here, we simulate each SN with a dependency (SN velocity) that has no corresponding model component in SALT2. Ejecta velocities are simulated according to the observed population from Siebert et al (2020).…”
Section: Fiducial+v Siii Simulationmentioning
confidence: 99%
See 1 more Smart Citation